1. Pendahuluan, Hak setiap peker ANALISIS POTENSI BAHAYA KERJA DENGAN METODE JOB SAFETY ANALYSIS (JSA) SEBAGAI UPAYA PENCEGAHAN KECELAKAAN DI PT X - Ardhiya Ulkhaq Nasrulloh; Aloysius Tommy Hendrawan; Erny Untari (Universitas Muhammadiyah Sorong, 2023)
PT X is a company engaged in the manufacture of white or granulated sugar. This company still has work accidents that often occur, caused by various factors including worker errors when carrying out work and the scope of work. So it is not uncommon for workers to get mild or moderate injuries, therefore an analysis of work accidents is carried out using the Job Safety Analysis (JSA) method. In this method can be known the type of accident, the cause of the accident, the consequences of the accident, and recommendations for improvement for the company. In this analysis, 3 work stations were carried out, namely 8 types of work accidents, 7 types of work accidents in the installation station, and 6 types of work accidents in the boiler station. This can be noticed by the company to pay more attention to workers, there are workers who do not use complete Personal Protective Equipment (PPE). the company must be more assertive if there are workers who do not use the complete PPE to be given an SP or a warning letter, in order to minimize the occurrence of work accidents in the company's scope of work.